Pegylated Liposomal Doxorubicin, Docetaxel, and Trastuzumab as Neoadjuvant Treatment for HER2-Positive Breast Cancer Patients: A Phase II and Biomarker Study - Wang, Haoqi; Li, Yuntao; Qi, Yixin; Zhao, Erbao; Kong, Xiangshun; Yang, Chao; Yang, Qiqi; Zhang, Chengyuan; Liu, Yueping; Song, Zhenchuan (Frontiers in Oncology, 2022)
Background: Trastuzumab based chemotherapy is the standard regimen for human epidermal growth receptor 2 (HER2) positive breast cancer (BC) in neoadjuvant therapy. Combination of trastuzumab and anthracycline is generally avoided clinically due to the cardiotoxicity.Concomitant administration of trastuzumab and anthracycline is generally avoided clinically due to the cardiotoxicity. Pegylated liposomal doxorubicin (PLD) is less cardiotoxic compared with traditional anthracyclines. Here, we conducted this prospective study to evaluate the efficacy, safety and potential biomarkers for PLD plus trastuzumab and docetaxel as neoadjuvant treatment in HER2 positive BC. Patients and methods: Patients with stage II or III HER2-positive BC were recruited in this multicenter, open-label, single-arm, phase II study. Eligible patients were given 6 cycles of PLD plus docetaxel and trastuzumab. Primary endpoint was totally pathological complete response (tpCR, ypT0/is ypN0). Secondary endpoints were breast pathological complete response (bpCR, ypT0/is), objective response rate (ORR), operation rate, breast-conserving surgery rate, and safety. Metadherin (MTDH), glutaminyl-peptide cyclotransferase (QPCT), topoisomerase II alpha (TOP2A), programmed death ligand 1 (PD-L1), and tumor-infiltrating lymphocytes (TILs) were evaluated in breast cancer tissues pre-neoadjuvant for potential biomarkers. Results: Between March 2019 and February 2021, 54 patients were enrolled, 50 were included in the analysis, and 35 (70.0%) completed 6 cycles of neoadjuvant treatment. Forty-nine (98.0%) patients underwent surgery with a breast-conserving rate of 44.0%. The tpCR, bpCR, and ORR we re 48.0% (95% CI, 33.7-62.6), 60.0% (95% CI, 45.2-73.6), and 84.0% (95% CI, 70.9%-92.8%), respectively. The tpCR was associated with MTDH (p=0.002) and QPCT (p=0.036) expression but not TOP2A (p=0.75), PD-L1 (p=0.155), or TILs (p=0.76). Patients with HR-negative status were more likely to achieve bpCR compared with HR-positive (76.2% vs. 48.3%, p=0.047). Grade ≥3 adverse events occurred in 38.0% of patients. Left ventricular ejection fraction decline by ≥10% was reported in 18.0% of patients, and no patients experienced congestive heart failure. Conclusions: PLD plus docetaxel and trastuzumab might be a potential neoadjuvant regimen for HER2-positive BC with high tpCR rate and manageable tolerability. MTDH and QPCT are potential predictive markers for tpCR.